The contribution of orthographic knowledge, phonological awareness, rapid automatized naming and phonological working memory to the reading skills of typically developing children - Mohammadi Najafabadi, Fariba; Soleymani, Zahra; Zadehlabbaf, Fariba; Kohansal, Azin (Applied neuropsychology. Child, 2025)
The present study examined the effects of orthographic knowledge (OK), phonological awareness (PA), rapid automatized naming (RAN), and phonological working memory (PWM) on the reading speed, accuracy, and comprehension of elementary school students. Results from a sample of 176 typically developing children in the second through fourth grades (mean age = 8.9 years) revealed that the correlation between reading and the other variables (PWM, PA, RAN, and OK) was significant. In Persian, which has an abjad writing system and opaque orthography, OK and RAN were the best predictors of reading. The relationship between reading skills and other factors was most evident in the fourth grade. We also found that female students in the fourth grade performed significantly better than male students on reading, RAN and OK. This study highlights of the fact that rapid naming and orthographic processing are more important than phonological processing for predicting reading skills in Persian.